2016
DOI: 10.1007/s00436-016-5213-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular survey of Ehrlichia canis and Coxiella burnetii infections in wild mammals of southern Italy

Abstract: Ehrlichiosis and Q fever caused by the intracellular bacteria Ehrlichia canis and Coxiella burnetii, respectively, are tick-borne diseases with zoonotic potential and widespread geographical distribution. This study investigated the prevalence of both infections in wild mammals in southern Italy. Tissue samples obtained from the red fox (Vulpes vulpes), European badger (Meles meles), gray wolf (Canis lupus), beech marten (Martes foina), and crested porcupine (Hystrix cristata) were processed for molecular dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 31 publications
1
18
1
2
Order By: Relevance
“…canis here found were identical to each other but differed from most of those previously found in foxes and wolves from southern Italy [5], confirming high intra-species variability of E . canis , irrespective of the geographical origin.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…canis here found were identical to each other but differed from most of those previously found in foxes and wolves from southern Italy [5], confirming high intra-species variability of E . canis , irrespective of the geographical origin.…”
Section: Discussionsupporting
confidence: 79%
“…canis detection only from red foxes ( Vulpes vulpes ) [710], although recently this bacterium has been detected in red foxes and wolves ( Canis lupus ) from southern Italy [5]. The high prevalence of infection found in wildlife carnivores in this latter study suggests that a sylvatic life cycle of this pathogen may occur.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…The infection rate of TBPs in red foxes is correlated with tick species and abundance in the environment, and with the infection rate of pathogens in ticks [ 30 , 32 , 42 ]. In previous European studies, blood or spleen samples of the red fox were found positive for several TBPs, namely A .…”
Section: Discussionmentioning
confidence: 99%